2022
DOI: 10.3389/fendo.2022.972341
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer subtypes based on the regulatory genes of RNA modifications: Novel prediction model of prognosis

Abstract: BackgroundOvarian cancer (OC) is a female reproductive system tumor. RNA modifications play key roles in gene expression regulation. The growing evidence demonstrates that RNA methylation is critical for various biological functions, and that its dysregulation is related to the progression of cancer in human.MethodOC samples were classified into different subtypes (Clusters 1 and 2) based on various RNA-modification regulatory genes (RRGs) in the process of RNA modifications (m1A, m6A, m6Am, m5C, m7G, ac4C, m3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 114 publications
0
7
0
Order By: Relevance
“…Previous studies found m7GRGs expression in ovarian cancer (OC) is significantly correlated with immune cells (involving CD4 + memory resting T cells, plasma cells, and Macrophages M1) (Zheng et al, 2022). In Hepatocellular carcinoma high m7G risk led to a decreased infiltration level of CD8 + T cells, whereas it increased the infiltration levels of Tregs and macrophages (Zhou et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies found m7GRGs expression in ovarian cancer (OC) is significantly correlated with immune cells (involving CD4 + memory resting T cells, plasma cells, and Macrophages M1) (Zheng et al, 2022). In Hepatocellular carcinoma high m7G risk led to a decreased infiltration level of CD8 + T cells, whereas it increased the infiltration levels of Tregs and macrophages (Zhou et al, 2022).…”
Section: Discussionmentioning
confidence: 94%
“…The four differentially expressed RNA-modification regulatory genes (DERRG) signature, comprising the Aly/REF export factor (ALYREF), ZC3H13, WTAP, and methyltransferase like 1 (METTL1), were recognized as a self-sufficient prognostic model in OC. This model is valuable for categorizing patients, assessing patient prognosis, and predicting patient response to immunotherapy in patients with OC ( 70 ). CACNA1G-AS1, ACAP2-IT1, AC010894.3, and UBA6-AS1 were discovered as prognostic signatures in OC, and each of these genes was associated with methyltransferase-like 5 (METTL5), RBM15, IGF2BP1, and YTH N6-methyladenosine RNA-binding protein C2 (YTHDC1), respectively, suggesting that they regulate the m6A regulatory gene ( 71 ).…”
Section: M6a Rna Modification Enzymes As Prognostic Biomarkers For Ocmentioning
confidence: 99%
“…The different expression patterns of RNA modification regulators between cancers and para‐cancerous tissues enable researchers to accurately make a differential diagnosis of benign and malignant diseases 434,435 . The relationship between RNA modification levels and patient prognosis presents great opportunities for patients with more precise prognosis evaluation and personalized therapies 436–439 . Additionally, in the era of precision medicine, the clinical significance of metabolism‐focused RNA methylation extends to the potential development of personalized treatment strategies.…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%
“… 434 , 435 The relationship between RNA modification levels and patient prognosis presents great opportunities for patients with more precise prognosis evaluation and personalized therapies. 436 , 437 , 438 , 439 Additionally, in the era of precision medicine, the clinical significance of metabolism‐focused RNA methylation extends to the potential development of personalized treatment strategies. Although current research is still in early stages and primarily focuses on basic investigations, numerous in vitro and in vivo assays have shown exhibited results for therapeutic approaches targeting RNA methylation in overcoming drug resistance in several cancer treatments.…”
Section: Rna Methylation and Cancer Metabolismmentioning
confidence: 99%